Random routing scheme with misleading dead ends - Chitra Rajarama; Jagadeesha Narasimhamurthy Sugatoor; Yerri Swamy T (International Journal of Informatics and Communication Technology (IJ-ICT), 2019)
A new method of sink location security in a Wireless Sensor Network is proposed. In the proposed scheme, all the node addresses are encrypted and an attacker cannot determine the real sink address by capturing the packets and analyzing its contents for the final destination. The main contribution of our proposed method is to use random routing scheme with misleading dead ends. This provides security against traffic analysis attack.